Clinical application status of wax therapy technology (蜡疗技术的临床应用现状) - WANG Chun (王纯); LU Lin (芦琳); TANG Ling (唐玲); LI Suqian (李苏茜) (中西医结合护理)
This paper introduced the origin of wax therapy technology and its clinical application in cervical spondylosis, osteoarthritis, gynecological diseases, skin diseases, nervous system and digestive system diseases. The clinical application status of wax therapy is summarized as follows, in order to provide more ideas and basis for clinical research. (本文总结了蜡疗技术的起源以及蜡疗技术在颈椎病、骨关节炎、妇科病、皮肤类疾病、神经系统、消化系统疾病中的临床应用, 以期为临床进一步完善蜡疗操作规范提供更多的思路与依据。)